2016
DOI: 10.5194/hess-20-2437-2016
|View full text |Cite
|
Sign up to set email alerts
|

An experimental seasonal hydrological forecasting system over the Yellow River basin – Part 1: Understanding the role of initial hydrological conditions

Abstract: Abstract. The hydrological cycle over the Yellow River has been altered by the climate change and human interventions greatly during past decades, with a decadal drying trend mixed with a large variation of seasonal hydrological extremes. To provide support for the adaptation to a changing environment, an experimental seasonal hydrological forecasting system is established over the Yellow River basin. The system draws from a legacy of a global hydrological forecasting system that is able to make use of realtim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 40 publications
(58 reference statements)
4
61
0
Order By: Relevance
“…However, over the northern and northwestern dry regions, the initial hydrologic conditions are expected to still strongly impact SM forecasts for longer lead times (three-month), particularly when the forecasts are initialized in dry (November-March) or wet-to-dry transition (October) months. In addition, in line with the previous findings [24], the summer RMSE ratio (June-August; orange lines) tends to converge at a specific value with increased lead times over the regions with strong seasonality in hydro-climate. This suggests that wet ICs will largely benefit the prediction of drought development and duration occurring at the end of the wet season.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…However, over the northern and northwestern dry regions, the initial hydrologic conditions are expected to still strongly impact SM forecasts for longer lead times (three-month), particularly when the forecasts are initialized in dry (November-March) or wet-to-dry transition (October) months. In addition, in line with the previous findings [24], the summer RMSE ratio (June-August; orange lines) tends to converge at a specific value with increased lead times over the regions with strong seasonality in hydro-climate. This suggests that wet ICs will largely benefit the prediction of drought development and duration occurring at the end of the wet season.…”
Section: Resultssupporting
confidence: 73%
“…In addition, the ESP/revESP diagnosis framework only focuses on two end points that reflect zero (i.e., directly taken from observational data) and perfect information (i.e., the ensemble taken from the full climatological period) of CFs and ICs, which prevents a comprehensive understanding of their relative roles at varying levels of uncertainty. What's more, the initial moisture storage only includes two primary state variables (SM and SWE), without consideration of other water storage components (e.g., surface water, groundwater), which could be important for one-month seasonal streamflow predictions in downstream regions [19,24]. This implies that more detailed components of initial storage, rather than the general SM and SWE, should be considered in future assessments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that state variables such as soil moisture or snow water equivalent can provide relevant information to extend predictability for lead times from one to several months ahead (e.g. Wood and Lettenmaier, 2008;Shukla et al, 2013;Yang et al, 2014;Yuan et al, 2016). The influence of initial conditions depends on the period of the year and on the location of watersheds (e.g.…”
Section: Introductionmentioning
confidence: 99%